Identification and characterization of Eci3, a murine kidney‐specific Δ3, Δ2‐enoyl‐CoA isomerase. Issue 3 (16th December 2013) - van Weeghel, Michel; Ofman, Rob; Argmann, Carmen A.; Ruiter, Jos P. N.; Claessen, Nike; Oussoren, Saskia V.; Wanders, Ronald J. A.; Aten, Jan; Houten, Sander M.
Abstract : Oxidation of unsaturated fatty acids requires the action of auxiliary enzymes, such as Δ 3, Δ 2 ‐enoyl‐CoA isomerases. Here we describe a detailed biochemical, molecular, histological, and evolutionary characterization of Eci3, the fourth member of the mammalian enoyl‐CoA isomerase family. Eci3 specifically evolved in rodents after gene duplication of Eci2. Eci3 is with 79% identity homologous to Eci2 and contains a peroxisomal targeting signal type 1. Subcellular fractionation of mouse kidney and immunofluorescence studies revealed a specific peroxisomal localization for Eci3. Expression studies showed that mouse Eci3 is almost exclusively expressed in kidney. By using immunohistochemistry, we found that Eci3 is not only expressed in cells of the proximal tubule, but also in a subset of cells in the tubulointerstitium and the glomerulus. In vitro, Eci3 catalyzed the isomerization of trans ‐3‐nonenoyl‐CoA to trans ‐2‐nonenoyl‐CoA equally efficient as Eci2, suggesting a role in oxidation of unsaturated fatty acids. However, in contrast to Eci2, in silico gene coexpression and enrichment analysis for Eci3 in kidney did not yield carboxylic acid metabolism, but diverse biological functions, such as ion transport ( P =7.1E‐3) and tissue morphogenesis ( P = 1.0E‐3). Thus, Eci3 picked up a novel and unexpected role in kidney function during rodent evolution.—van Weeghel, M., Ofman, R., Argmann, C. A., Ruiter, J. P. N., Claessen, N., Oussoren, S. V., Wanders, R. J. A., Aten, J., Houten, S. M. Identification and characterization of Eci3, a murine kidney‐specific Δ 3, Δ 2 ‐enoyl‐CoA isomerase. FASEB J. 28, 1365–1374 (2014). www.fasebj.org